Novel functions of inactive rhomboid proteins in immunity and disease. Issue 4 (1st August 2019) - Geesala, Ramasatyaveni; Issuree, Priya D.; Maretzky, Thorsten
Abstract: iRhoms are related to a family of intramembrane serine proteinases called rhomboids but lack proteolytic activity. In mammals, there are two iRhoms, iRhom1 and iRhom2, which have similar domain structures and overlapping specificities as well as distinctive functions. These catalytically inactive rhomboids are essential regulators for the maturation and trafficking of the disintegrin metalloprotease ADAM17 from the endoplasmic reticulum to the cell surface, and are required for the cleavage and release of a variety of membrane‐associated proteins, including the IL‐6 receptor, l ‐selectin, TNF, and EGFR ligands. iRhom2‐dependent regulation of ADAM17 function has been recently implicated in the development and progression of several autoimmune diseases including rheumatoid arthritis, lupus nephritis, as well as hemophilic arthropathy. In this review, we discuss our current understanding of iRhom biology, their implications in autoimmune pathologies, and their potential as therapeutic targets. Abstract : Review on the role of inactive rhomboids in animal disease models and their implications in human autoimmune diseases.